Privatization and Restructuring : An Incomplete-Contract Approach - Bos, Dieter (IMF Working Papers; Working Paper, 1996)
Since an enterprise, which is to be privatized, has to be restructured in uncertainty, and the restructuring investments are sunk when the final decision on the sale price is taken, there is an imminent danger that restructuring is not efficient, and there is underinvestment. We consider, restructuring by the private buyer of the firm, by a government privatization agency, and by both. In the first two cases-one-sided restructuring-a first best can be achieved. In the case of both-sided restructuring, however, the first best cannot be reached if both parties engage in restructuring after signing the contract.